2015
DOI: 10.1017/s1049023x15000114
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Preventable Disaster Death at Medical Institutions in Areas Affected by the Great East Japan Earthquake: A Retrospective Preliminary Investigation of Medical Institutions in Miyagi Prefecture

Abstract: Preventable disaster death at medical institutions in areas affected by the Great East Japan Earthquake occurred mainly at coastal hospitals. Insufficient resources (at GHs), environmental factors (at coastal hospitals), and delayed medical intervention (at all hospitals) constituted the major potential contributing factors. Further investigation of all medical institutions in Miyagi Prefecture, including those with fewer than 20 patient deaths, is required in order to obtain a complete picture of the details … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Yamanouchi et al . also elucidated that one of the main causes of preventable disaster deaths was deteriorated environmental conditions in homes and emergency shelters at the coastal area in the GEJE [28]. In another original cohort study, Takahashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Yamanouchi et al . also elucidated that one of the main causes of preventable disaster deaths was deteriorated environmental conditions in homes and emergency shelters at the coastal area in the GEJE [28]. In another original cohort study, Takahashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…2 In comparison with reports of earthquake damage from largescale earthquake disasters that have occurred globally since 2000 (eg, the 2004 Indian Ocean Earthquake, a M9.1 earthquake that occurred off the coast of Sumatra in which approximately 286,000 people perished, over 283,000 of whom died in the resulting tsunami; 3 the 2008 Sichuan Earthquake, a M8.0 earthquake that occurred in China's Sichuan Province, claiming over 69,000 lives, 60,000 of whom died by being crushed under falling buildings; 4 and the 2010 Haiti Earthquake, a M7.0 earthquake that occurred in the Republic of Haiti, claiming between 10,000 and 31,600 lives, the majority of whom died by being crushed under falling buildings 5 ), a characteristic of the Great East Japan Earthquake was that it occurred during winter in a cold region and was accompanied with extensive tsunami damage. 6 In addition, with regard to preventable disaster deaths (PDDs), the authors previously reported the results of a retrospective preliminary investigation of Miyagi Prefecture (Japan), which experienced the highest numbers of dead or missing people during the Great East Japan Earthquake. 6 Preventable disaster deaths were defined as "deaths occurring during a disaster that would have been preventable under normal regional and hospital environmental conditions and medical systems," and the 25 hospitals selected for inclusion in the study were either disaster base hospitals (DBHs) or those that had experienced at least 20 patient deaths between March 11, 2011 and April 1, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition, with regard to preventable disaster deaths (PDDs), the authors previously reported the results of a retrospective preliminary investigation of Miyagi Prefecture (Japan), which experienced the highest numbers of dead or missing people during the Great East Japan Earthquake. 6 Preventable disaster deaths were defined as "deaths occurring during a disaster that would have been preventable under normal regional and hospital environmental conditions and medical systems," and the 25 hospitals selected for inclusion in the study were either disaster base hospitals (DBHs) or those that had experienced at least 20 patient deaths between March 11, 2011 and April 1, 2011. Preventable disaster deaths at medical institutions in areas affected by the Great East Japan Earthquake occurred mainly at coastal hospitals, with delayed medical intervention and a lack of resources in the medical facilities constituting the major potential contributing factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Japan had prepared the disaster medical response system after experiencing the Great Hanshin Awaji Earthquake (GHAE) in 1995 when the "preventable disaster death" was recognized for the first time (Yamanouchi et al 2015). Japanese disaster medical system has following five fundamental structures;…”
Section: Introductionmentioning
confidence: 99%